ANALISIS PENERAPAN RULE OF LAW OLEH MAHKAMAH KONSTITUSI SEBAGAI THE GUARDIAN OF CONSTITUTION (Studi Kasus Putusan MK Nomor 90/PUU-XXI/2023) - Fiqih, Pramesti Ratu; Widodo, Adellia Mahardhika; Firdaus, Anisa Miftahul (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
The issuance of the Constitutional Court Decision Number 90/PUU-XXI/2023 reaped the pros and cons from various parties. The Constitutional Court's Decision Number 90/PUU-XXI/2023 contains elements of intervention outside the judiciary and/or personal interests, thus raising big questions about the independence of the exercise of judicial power by the Constitutional Court. Indonesia applies the principle of the Rule of Law and encourages law enforcement which not only guarantees formal rights but also guarantees justice in real life for everyone. However, Indonesian law has not been fully able to become a rule of social justice, because law enforcement officers and legal issues are closely related to the ethics of law enforcement and the community itself. This research uses a normative legal research type, where the author uses a case approach, where the author uses an inkracht court decision and a statute approach. The results of this study explained that the issuance of the Constitutional Court decision Number 90/PUU-XXI/2023 was not in line with the principles of the Rule of Law, because it was felt that the decision removed the nickname of the Constitutional Court as The Guardian Of the constitutions. The decision is considered destructive to the constitution because it reaps the pros and cons in society, they think that the Constitution becomes a political container. the application of the Rule of Law principle by constitutional judges is very important to maintain justice, integrity, and public trust in the legal system. If the judge's decision is not in accordance with the Rule of Law, various negative consequences can occur, including erosion of public trust, injustice, legal uncertainty, abuse of power, human rights violations, obstacles to legal reform, and social and political instability. Therefore, it is important to ensure that MK judges work independently, transparently, accountable, and based on clear and fair legal principles.